Food particularity and sprey trout migrations on the territory of the Chechen Republic - M. G. Kaimov; R. H. Gairabekov (Юг России: экология, развитие, 2015)
The stream trout is one of the kind preferring pure ecological conditions, according to this kind maybe an indicator of ecological condition of environment in the Chechen Republic. That’s why studying biology of this kind is actual, to find out its condition in present.